Newton, I. (1982). Principios matemáticos de la filosofía cultural y su sistema del mundo. Edición preparada por Antonio Escohotado, Madrid, Editora Nacional. 906 págs. - Editor, El; Pontificia Universidad Javeriana (2016)
null